World Englishes Representation in English Textbooks of Indonesian Elementary Schools - Annisa, Rifka Nida; Gusdian, Rosalin Ismayoeng (Universitas Muhammadiyah Malang, 2023)
This study aimed at investigating the representation of World Englishes (WE) in English textbooks used in elementary schools in Indonesia. Two English books for a sixth-graders were used as the data sources. This study used qualitative approach and document analysis as the method to gather the data. The collected data were then analyzed based on Braj Kachru's theory of World Englishes comprising inner, outer, and expanding circles. The analyzed data were eventually validated by the experts in the field of applied linguistics. The findings show that the inner circle and expanding circle representations are found in these two books. The representation of both circles was reflected from pictures and reading texts. Meanwhile, the outer circle did not acquire ample depiction in both books. In conclusion, the effort of introducing WE to elementary school students has been presented in the text books that were dominated by expanding circles based on the research in this study case.